Using Team Assisted Individualization Method to Improve Students’ Writing Skill - Mutia, Utin; Mariska, Deby (EEdJ: English Education Journal, 2022)
The aim of this study was to know the implementation of Team Assisted Individualization Method in improving students’ skill in Writing Skill of Recount text and to find out the significant difference of the skill in Writing of recount text between the students by using Team Assisted Individualization and those who are not. The subject of this study were the students of eighth grade students of SMPN 4 Kelapa in academic year 2021/2022. In this study, the researcher used quantitative approach with quasi-experimental design. The population of the research are the students among the eight grade of SMPN 4 Kelapa which consist of 53 students. and the sample is the class VIII grade students which also consist of 53 students. Based on the fact, it could be concluded that there was a significant difference between the samples significantly, and Team Assisted Individualization improved the students’ skill in Writing of recount text. Therefore, the result of this study is expected to contribute to the development of the process of English teaching and learning, epecially for teaching and learning writing skill.